Probabilistic Analysis to Quantify the Effect of the Use of a Material Transfer Device on a Smoothness Pay Incentive. Issue 1 (2016) - Kwon, Ohhoon; Lee, Hyung Suk; Greene, James; Choubane, Bouzid; Hewitt, Richard M.
Use of a material transfer device (MTD) during asphalt paving to provide smoother pavement while eliminating thermal and material segregation is well known. However, the additional operating cost may prevent contractors from investing in an MTD. This study evaluated the effect of MTDs on the smoothness of the finished friction course layer and predicted the incentives or disincentives a contractor may receive by using an MTD. Two empirical models were developed by using simple linear regression analysis to predict the smoothness of the final friction course on the basis of the underlying structural layer smoothness and whether or not an MTD was used. The regression model results were used in Monte Carlo simulations in conjunction with residual analysis techniques to predict, in a probabilistic fashion, the incentives or disincentives that a contractor could receive as a result of the Florida Department of Transportation's new developmental specification for smoothness. Finally, expected incentives were predicted as a simulation result. Two validation projects with a normalized length of 10 mi showed additional expected incentives of 9, 700 and 10, 000 when an MTD was used compared with the expected incentives when an MTD was not used. The additional incentives were approximately 30% more than the typical operating cost of an MTD for construction of a 10 lane miles long friction course in Florida.